From Infection to Autoimmunity: S. pyogenes as a Model Pathogen - Virginia Girlando; Luisa De Angelis; Gianluca D’Egidio; Armando Di Ludovico; Luciana Breda (Microorganisms)
Group A β-hemolytic Streptococcus (GAS) is a Gram-positive, coccoid-shaped bacterium that tends to grow in chains; it is a non-spore-forming, facultatively anaerobic, catalase-negative, aerobic bacterium. It is known to cause a wide range of infections in children, ranging from mild upper respiratory tract infections, such as pharyngitis, to severe invasive disease. GAS also notably triggers post-infectious immune sequelae, including acute poststreptococcal glomerulonephritis (APSGN), acute rheumatic fever (ARF), and rheumatic heart disease (RHD), which are major health burdens, especially in low-income countries. In this review, we will present the general characteristics of GAS, highlighting its structural and microbiological features. We will also discuss its pathogenetic mechanisms, especially molecular mimicry, and its ability to cause autoimmune responses. Finally, we will elucidate some of the autoimmune sequelae that mark GAS infections, such as ARF, RHD, APSGN, and guttate psoriasis. Understanding GAS as a model pathogen for infection-induced autoimmunity provides insight into host–pathogen interactions and supports the development of targeted interventions. Emphasis on early diagnosis and antibiotic treatment is essential to reduce the burden of autoimmune complications